2003
DOI: 10.1097/01.tp.0000074360.62032.39
|View full text |Cite
|
Sign up to set email alerts
|

Long-term improvement in renal function with sirolimus after early cyclosporine withdrawal in renal transplant recipients: 2-year results of the rapamune maintenance regimen study1 2

Abstract: Data at 2 years confirm that early CsA withdrawal followed by an SRL-ST maintenance regimen results in long-term improvement in both renal function and blood pressure, without increased risk of graft loss or late acute rejection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(106 citation statements)
references
References 14 publications
5
98
1
2
Order By: Relevance
“…As a result, the strategy of CNI elimination, which comprised the vast majority of the Withdrawal cohort, may not produce similar outcomes in patients on more standard CNI/MMFbased immunosuppression (28,29). There are other limitations of this study.…”
Section: Discussionmentioning
confidence: 78%
“…As a result, the strategy of CNI elimination, which comprised the vast majority of the Withdrawal cohort, may not produce similar outcomes in patients on more standard CNI/MMFbased immunosuppression (28,29). There are other limitations of this study.…”
Section: Discussionmentioning
confidence: 78%
“…Because of its power to suppress acute rejections, the substance is currently under investigation in calcineurin-inhibitor-sparing regimens after kidney transplantation. Replacement of the nephrotoxic agents by rapamycin might reduce the risk for chronic allograft dysfunction and could thereby lead to an overall improvement of kidney graft survival [3,4]. However, many physicians express their concerns that the withdrawal of calcineurin inhibitors, which have substantially contributed to the success of organ transplantation in general, might put their patients at risk of insufficient immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…3 This complication was surprisingly not reported in de novo trials using SRL before approval for clinical use, but the reason for that was that this parameter was not evaluated in those trials. Especially the Rapamune Maintenance Regimen (RMR) trial demonstrated a significant improvement in renal function after early cyclosporine (CyA) elimination in a regimen including SRL, a better pathological profile at 3 years postransplant and better graft survival at 4 years postransplant [5][6][7][8] …”
mentioning
confidence: 99%